'The Conversion of the Barbarians': Comparison and Psychotherapists' Approaches to Buddhist Traditions in the United States. (28th October 2015) - Helderman, Ira
Abstract : The use of Buddhist teachings and practices in psychotherapy, once described as a new, popular trend, should now be considered an established feature of the mental health field in the United States and beyond. Religious studies scholars increasingly attend to these activities. Some express concern about what they view as the secularizing medicalization of centuries old traditions. Others counter with historical precedent for these phenomena comparing them to previous instances when Buddhist teachings and practices were introduced into new communities for healing benefit like medieval China. I reveal that a growing number of clinicians also describe their activities in comparison to moments of Buddhist transmission like medieval China. Drawing on the models of scholars like Robert Ford Campany and Pierce Salguero, I outline the possible benefits and limits of such comparisons. I ultimately conclude that scholars use comparison to normalize these contemporary phenomena as cohering to a historical pattern and their interpretations are subsequently employed by clinicians to legitimate their activities.